FORMATION OF THE PORTFOLIO OF DIGITAL MARKETING TOOLS OF THE ENTERPRISE UNDER THE RECOVERY OF THE ECONOMY OF UKRAINE - Larka , LUDMILA (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the peculiarities of the period of post-war recovery of the Ukrainian economy and their influence on the composition of the portfolio of digital marketing tools of enterprises. The purpose of the article is to develop an algorithm for forming a portfolio of digital marketing tools for an enterprise in the period of post-war recovery, to clarify the concept of a "portfolio of digital marketing tools of an enterprise." It is substantiated that in the post-war period, the provisions of the concept of anti-crisis marketing will be relevant for planning the marketing activities of enterprises. The most common digital marketing tools are identified. The definition of the term "portfolio of digital marketing tools of the enterprise" is proposed. An algorithm for forming a portfolio of enterprise digital marketing tools has been developed. It was determined that the audit of the enterprise’s marketing activity is the foundation for the formation of the enterprise’s portfolio of digital marketing tools. It was determined that conducting marketing research will contribute to increasing the accuracy of the planning of the enterprise’s anti-crisis marketing program. It is proposed to apply decision-making criteria in conditions of uncertainty and risk when choosing optimal alternatives for achieving the company’s marketing goals in the post-war period. It was determined that monitoring the level of rationality of the company’s portfolio of digital marketing tools is a necessary condition for controlling the company’s marketing activities. The expediency of focusing on a proactive strategy in the implementation of marketing activities has been investigated. It has been studied that in recent years the tools of digital marketing have been constantly improved and this allows it to be considered as an opportunity to spend the marketing budget of enterprises more rationally. The portfolio of digital marketing tools can include content marketing, SEO, contextual and targeted advertising, advertising in social networks, e-mail marketing, influencer marketing, lead generation, complex analytics, viral marketing.